Level of Knowledge and Practice of Patient Care Ethics among Nurses in Pokhara - Timilsina, Arati; KC, Bhagawati (Janapriya Journal of Interdisciplinary Studies, 2018)
Ethics deal with standards of conduct and moral judgment. Every day nurses require to make ethical decisions during patient care. They should have good knowledge and adequate practice of ethics to make ethical decisions. The aim of this study was to identify the knowledge and practice of patient care ethics among nurses. A descriptive cross sectional research design was used to conduct the study. Simple random sampling method was adopted to select 108 nurses among 133 nurses working in a regional hospital, Pokhara. Self-administered structured questionnaire schedule was used for data collection and analyzed using IBM SPSS Version 20. Descriptive and inferential statistics such as frequency, percentage, mean, standard deviation, Chi-square test was used to analyze the data. The findings revealed that 65.1 percent of nurses had satisfactory level knowledge and 76.4 percent had adequate practice level of patient care ethics. There was significant association between nurses knowledge level and professional qualification (p